Perspectives of Psychotherapists and Psychiatrists on Mental Health Care Integration Within Primary Care Via Video Consultations: Qualitative Preimplementation Study - Hoffmann, Mariell; Wensing, Michel; Peters-Klimm, Frank; Szecsenyi, Joachim; Hartmann, Mechthild; Friederich, Hans-Christoph; Haun, Markus W (JMIR Publications, 2020)
BackgroundMany patients with mental disorders remain untreated. Video-based mental health care demonstrates comparable effectiveness to face-to-face treatments and is a promising mode for delivering specialized care within primary care. Nevertheless, professionals struggle with implementing video consultations in their daily practice. Specifically, little is known about mental health specialists' acceptance of mental health video consultations in routine practice. The PROVIDE (ImPROving cross-sectoral collaboration between primary and psychosocial care: An implementation study on VIDEo consultations) project aims to improve cross-sectoral collaboration between primary and psychosocial care through implementing video consultations in primary care. To increase the uptake of video consultations, it is crucial to account for necessary prerequisites and to tailor interventions to the needs of the target group prior to implementation. ObjectiveThe aim of this study was to explore the acceptance of video consultations embedded in primary care from the perspectives of mental health specialists in Germany. MethodsWe conducted a qualitative, exploratory, preimplementation study in urban and rural counties. We conducted three semistructured focus groups with 11 mental health specialists. We used qualitative content analysis combining an inductive-deductive approach, applying the Tailored Implementation in Chronic Diseases (TICD) framework to the text material, which comprises individual health professional factors; patient factors; professional interactions; incentives and resources; capacity for organizational change; social, political, and legal factors; and guideline factors. ResultsAgainst the background of long waiting times and a shortage of mental health specialists, especially in rural areas, participants valued video consultations as a potential means to improve access to mental health care. With respect to the TICD framework domains, the participants most often discussed individual health professional factors, followed by patient factors. All participants highlighted the importance of a trusting relationship between the patient and the therapist and doubted whether such a relationship could be established through video consultations (11/11, 100%). However, participants considered mental health specialist video consultations to be particularly suited for patients in rural areas, those with impaired mobility, and those who may otherwise remain untreated (6/11, 55%). Most participants expected video consultations to help the aforementioned patient groups avoid tedious searching for an available therapist and save on travel time and, therefore, improve access to specialized care for patients (7/11, 64%). Moreover, the participants expected video consultations to improve collaboration with the family physician (6/11, 55%). Finally, participants identified organizational aspects, such as reliable scheduling, the duration of the individual consultation (9/11, 82%), and reimbursement conditions (7/11, 67%), as key drivers for the acceptance and adoption of the model. ConclusionsWhile mental health specialists expect video consultations to improve access to specialized care for some patients, they consistently wonder whether such consultations can establish a trusting patient-therapist relationship. When implementing video consultations, these concerns should be addressed by training providers in managing technology-based treatment settings, with extra consideration for fostering the patients' and therapists' engagement. Trial RegistrationGerman Clinical Trials Register DRKS00012487; https://tinyurl.com/uhg2one